Elaboración de un manual de seguridad y salud del trabajo para los Laboratorios Agroindustriales de Química General de la ESPAM MFL. - Reyna Párraga, Adriana Magdalena (2015)
The development of the research focuses on the development of a Manual for Safety and Health at Work for agro-chemical laboratories General of the Technical College of Agricultural Manuel Felix Lopez Manabí, in order to analyze and identify workplace hazards found. The application of agro-industrial processes on General Chemistry Laboratory was used as research methodology and learning and certainly through the execution of this manual could establish the risks in the laboratories of the company analyzed. The methods used were: descriptive method based on the search for information, the analytical method and the historic allowed to analyze the current situation and historical data. The research used was field research, literature and analytics. Research techniques were observation, survey, interview and occupational risk matrix was an important tool in the investigation which offered solutions and improvements of safety and health at work; analyzing and identifying risk factors that occur in the workplace. Ultimately obtaining the conclusions and recommendations of the study object. Thus it was concluded that in carrying out this methodology, the manual helped ESPAM "MFL"; have a very important tool when it comes to the safety of employees of the entity, to safeguard the health of staff and integrity.